Outcome of Supracostal Access of Percutaneous Nephrolithotomy in Pediatric Population - A Single Centre Experience (Medical Forum Monthly, 2024)
Objective: Despite lower complication rates reported in adults, the supracostal approach remains underutilized globally. This study aims to assess the safety and efficacy of this approach in pediatric patients.Study Design: Retrospective, Observational studyPlace and Duration of Study: This study was conducted at the Department of Urology, The Kidney Centre, Post Graduate Training Institute, Karachi, Pakistan between January 1st 2023 till March 31st 2024.Methods: Patients under 17 years old who underwent PCNL via supracostal puncture were included, while those above 17 years old, underwent multiple procedures simultaneously, or those with any renal anomalies were excluded. All PCNL procedures were conducted with the patient in a prone position. Puncture was carried out using an 18-gauge LP needle under fluoroscopic guidance. Data, including post-operative morbidity, stone-free rates, operative time, stone burden, and hospital stay, were analyzed using SPSS v21.Results: The total number of patients included in the study was 211. The Median age of the patients was 6 years. The median stone size was 1.5 (1.3-1.9) cm. Mild haematuria was observed in 8 patients (3.8%), while only 1 patient had moderate haematuria (0.5%). The mean difference between the pre and postoperative haemoglobin was 0.6g/dl. Pleural effusion was observed in five patients (2.4%). The mean postoperative hospital stay was 3.8 ±0.4 days.Conclusion: Supracostal PCNL is a safe and effective approach for complex renal stones in a paediatric population.